The Growth of Sea cucumber Stichopus herrmanni After Transverse Induced Fission in Two and Three Fission Plane - Retno Hartati; Widianingsih Widianingsih; Hadi Endrawati (Marine Science Department Diponegoro University, 2016)
Transverse induced fission proven could be done in Teripang Tril, Stichopus herrmanni. This present works aimed to analyze wound recovery, regeneration period and growth of Teripang Trill after asexual reproduction by fission using two and three fission plane. Observations were made every day until the sea cucumber body separated into two or more (depending on treatment) and reared for 16 weeks. The results showed that there are differences in wound recovery, regeneration period and growth of S. herrmanni depend on their different fission plane. The wound recovery and regeneration period (days) of anterior, middle and posterior individu S. herrmanni resulted from two and three fission plane were varied but the two fission plane the anterior individu recover for longer period than posterior part and the wound recover process in both end for thee fission plane was same. Average growth of anterior and posterior fragment were longer for two fission plane than three fission plane. The middle fragment (M1 and M2) both fission plane was able to grow but very low. It showed that three fission plane gave very slow growth in every fragment of the body. Keywords: growth, post-fission, fission plane, Stichopus herrmanni